Nurses’ Empathy, Burnout, and Contentment with Life in Turkey - Mersin, Sevinç; İbrahimoğlu, Özlem; Tuncer, Merve; Arslanoğlu, Ali (UI Scholars Hub, 2024)
Background: Empathy has various consequences for nurses. Therefore, its effects on nurses should be identified. Thus, this study aimed to determine the relationships between empathy, burnout, and level of contentment with life in nurses and the characteristics that affect them. Methods: This descriptive–correlational study was conducted on 653 nurses in Turkey between November and December 2021. Data were collected using an information form, the Basic Empathy Scale, Burnout Measure Short Scale, and Contentment with Life Assessment Scale. Results: A positive, weak, and significant relationship was noted between the mean Basic Empathy Scale and Burnout Measure Scale scores. A significant negative and moderately strong relationship was found between the mean Burnout Measure Scale and Contentment with Life Assessment Scale scores. Conclusions: It is crucial that the increase in the level of empathy in nurses also increases their level of burnout. Therefore, examining the empathy skills of nurses through in-depth interviews may be indicated, as well as revealing the reasons for the effect of empathy on burnout. The results of this study can be beneficial for planning interventions to reduce burnout levels in nurses.